2014
DOI: 10.1007/s10532-014-9714-1
|View full text |Cite
|
Sign up to set email alerts
|

Bench-scale biodegradation tests to assess natural attenuation potential of 1,4-dioxane at three sites in California

Abstract: 1,4-Dioxane (dioxane) is relatively recalcitrant to biodegradation, and its physicochemical properties preclude effective removal from contaminated groundwater by volatilization or adsorption. Through this microcosm study, we assessed the biodegradation potential of dioxane for three sites in California. Groundwater and sediment samples were collected at various locations at each site, including the presumed source zone, middle and leading edge of the plume. A total of 16 monitoring wells were sampled to prepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Chemical oxidation like chlorination (Klečka and Gonsior, 1986) and advanced oxidation techniques are impractical for remediating large diluted plumes (Adams et al, 1994;Félix-Navarro et al, 2007;Stefan and Bolton, 1998). Similarly, while natural attenuation is possible for 1,4-dioxane, it is not ubiquitous (Chiang et al, 2012;Li et al, 2013Li et al, , 2014Sei et al, 2010). However, 1,4-dioxane is biodegradable.…”
Section: Introductionmentioning
confidence: 99%
“…Chemical oxidation like chlorination (Klečka and Gonsior, 1986) and advanced oxidation techniques are impractical for remediating large diluted plumes (Adams et al, 1994;Félix-Navarro et al, 2007;Stefan and Bolton, 1998). Similarly, while natural attenuation is possible for 1,4-dioxane, it is not ubiquitous (Chiang et al, 2012;Li et al, 2013Li et al, , 2014Sei et al, 2010). However, 1,4-dioxane is biodegradable.…”
Section: Introductionmentioning
confidence: 99%
“…Chiang et al (2006Chiang et al ( , 2007Chiang et al ( , 2008 reported a similar half-life was required in attempts to model a 1,4-dioxane plume from a manufacturing facility. Li et al (2015a) found 1,4-dioxane biomarkers present at three of four California sites, and Li et al (2014Li et al ( , 2015b found native degraders at multiple sites were capable of degrading 1,4-dioxane in microcosms. More work is required in this area because the findings above are somewhat in conflict with the conventional wisdom regarding degradation of 1,4-dioxane.…”
Section: Phytoremediationmentioning
confidence: 96%
“…Li et al. () found 1,4‐dioxane biomarkers present at three of four California sites, and Li et al. (, ) found native degraders at multiple sites were capable of degrading 1,4‐dioxane in microcosms.…”
Section: Overview Of Sustainability Drivers By Technologymentioning
confidence: 99%
“…A second data mining effort that estimated decline in concentrations in wells over time suggested DX was degrading at rates similar to groundwater contaminants that are known to degrade, such as commingled chlorinated VOCs (Adamson et al, 2015). A study of DX groundwater sites in California indicated evidence of DX degraders present at all three sites (Li et al, 2014). In microcosm studies performed at Rice University, DX concentrations declined over time relative to killed control microcosms, suggesting biodegradation was active at these sites.…”
Section: Natural Attenuationmentioning
confidence: 99%